2011
DOI: 10.1021/ma2014595
|View full text |Cite
|
Sign up to set email alerts
|

Chain Growth Polymerization of Isoprene and Stereoselective Isoprene–Styrene Copolymerization Promoted by an ansa-Bis(indenyl)allyl–Yttrium Complex

Abstract: The ability of rac-[{Me2C(Ind)2}Y(1,3-(SiMe3)2C3H3)] (Ind = 9-indenyl) (1) to catalyze isoprene polymerization, either as a single-site component or in combination with an alkyl–metal as a chain transfer agent (CTA) via coordinative chain transfer polymerization (CCTP), has been investigated. Complex 1 alone catalyzes the highly 1,4-trans-stereoselective polymerization of isoprene with moderate activity. The addition of ZnEt2 provides an efficient catalytic system for the reversible CCTP of isoprene with reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 94 publications
1
36
0
Order By: Relevance
“…By adjusting the amount of Mg(nBu) 2 , up to 200 polymer chains can be generated per metal center, and good control of the molecular weight features enables the tailoring of low to medium molecular weight polymers. The same system proved effective also for the CGP of isoprene and isoprene-styrene, yet with the 1,4-trans specificity gradually decreasing in favor of the 3,4-polymer with increasing amounts of Mg(nBu) 2 [20]. Finally, it is noteworthy that, in contrast to Mg(PE) 2 species, the isolation and further manipulation of the Mg(polystyryl) 2 and Mg(polydienyl) 2 species generated in these Ln-Mg-mediated CGP processes remains to be demonstrated.…”
Section: Chain Growth Polymerization Of Ethylenementioning
confidence: 94%
See 1 more Smart Citation
“…By adjusting the amount of Mg(nBu) 2 , up to 200 polymer chains can be generated per metal center, and good control of the molecular weight features enables the tailoring of low to medium molecular weight polymers. The same system proved effective also for the CGP of isoprene and isoprene-styrene, yet with the 1,4-trans specificity gradually decreasing in favor of the 3,4-polymer with increasing amounts of Mg(nBu) 2 [20]. Finally, it is noteworthy that, in contrast to Mg(PE) 2 species, the isolation and further manipulation of the Mg(polystyryl) 2 and Mg(polydienyl) 2 species generated in these Ln-Mg-mediated CGP processes remains to be demonstrated.…”
Section: Chain Growth Polymerization Of Ethylenementioning
confidence: 94%
“…In the global context of sustainable development stigmatized by the depletion of the reserves of fossil fuel and the ever-increasing prices of oil-derived materials, linear (19) by Gibson and coworkers [38] and related bis(pyridylamine) magnesium isopropyl complexes (20) by Carpentier and coworkers [39] for the polymerization of MMA Alkaline-Earth Metal Complexes in Homogeneous Polymerization Catalysisaliphatic poly(ester)s and poly(carbonate)s prepared by ROP of cyclic (di)esters and carbonates are attracting growing attention as both commodity and specialty materials. They are often biocompatible and biodegradable, and offer thermal, physical, and mechanical properties which are complementary or comparable to those of some oil-based polymers [40][41][42][43][44][45].…”
Section: Polymerization Of Cyclic Esters and Carbonates: General Aspectsmentioning
confidence: 99%
“…The ansa-lanthanidocene allyl rac-{Me2C(Ind)2}Y[ 3 -1,3-(SiMe3)2C3H3] (9Y) (Ind = 2-indenyl) was assessed for the polymerization of isoprene [32]. This compound was synthesized previously and initially evaluated for styrene polymerization as single-component catalyst [31].…”
Section: Allyl Complexes For the Polymerization Of Styrenementioning
confidence: 99%
“…By adjusting the amount of Mg( n Bu) 2 , up to 200 polymer chains can be generated per RE center. Complex 9 Y was previously shown to be active as a single-component catalyst [32], but the dispersity was improved in the presence of excess Mg( n Bu) 2 . Mechanistic investigations, also confirmed by the support of theoretical studies, demonstrated that the initiation of the polymerization resulted from the insertion of styrene into the RE-allyl (single component) or RE-alkyl (chain transfer) moiety, and that an enantiomorphic site control mechanism (ECM) was operative to account for the isoselectivity observed [39].…”
Section: Allyl Complexes For the Polymerization Of Styrenementioning
confidence: 99%
“…Yttrium complex 47 bearing a C 2 ‐symmetric rac ‐Me 2 C(Ind) 2 ligand could obtain trans ‐1,4‐PIP‐ co ‐iPS diblock or multiblock copolymers via either sequential or simultaneous copolymerization method. Typical plastic properties of well‐defined trans ‐1,4‐PIP‐ b ‐iPS diblock copolymers were featured because of their two crystalline chain segments …”
Section: Polymerization Of Styrene and Substituted Styrenementioning
confidence: 92%